2017
DOI: 10.4186/ej.2017.21.7.75
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Dynamics Bed Shear Stress Distribution around a Circular Cylinder Using Various Turbulences Models

Abstract: Abstract. Scouring around cylinders is greatly affected by the value of bed shear stress entered on sediment materials of the bed. Regarding the importance of the bed shear stress fluctuations and their influence on the initiation and development of scouring around cylinders, in this paper, the dynamic bed shear stress distributions around a circular cylinder in high Reynolds numbers flow is investigated using various turbulence closures. Since the bed shear stress can be regarded as one of the key parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The results showed that when a cylindrical pillar was placed at 60 o , there was the deepest scouring and that when the discharge was greater, so too was the scouring. The scouring that occurred around the pillars was also affected by the baseline flow shear stress [13]. Ishak [14] studied the water surface around a U-shaped channel bend (180 o ), with variations of 30 o .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that when a cylindrical pillar was placed at 60 o , there was the deepest scouring and that when the discharge was greater, so too was the scouring. The scouring that occurred around the pillars was also affected by the baseline flow shear stress [13]. Ishak [14] studied the water surface around a U-shaped channel bend (180 o ), with variations of 30 o .…”
Section: Introductionmentioning
confidence: 99%